إدارة إمداد المنطقة الساحلية بمياه الشرب من نبع السن باستخدام برنامج WEAP21 - سلمان, هناء; الأسعد, علي محمد; الحطاب, رنيم سلمان (Latakia University Journal -Engineering Sciences Series, 2019)
يعد نبع السن من أهم مصادر المياه العذبة في القطر العربي السوري، ويشكل المصدر الأساسي في الساحل السوري لتأمين مياه الشرب والاستخدام المنزلي لمدن اللاذقية، طرطوس، جبلة، القرداحة، الحفة والكثير من القرى التابعة لها، إضافة إلى تأمينه حاجات الزراعة وري مساحات شاسعة من سهول جبلة وتلبيته لحاجات الصناعة سواءً لمصفاة بانياس أو للعديد من المعامل، وأهمية هذا المصدر المائي تقتضي اتخاذ كافة الإجراءات لحمايته من حدوث عجز مستقبلي في قدرته على التزويد بالمياه بالكمية والنوعية والزمن المناسب. لذا تم استخدام نظام تخطيط وتقييم المياه WEAP21 لبناء نموذج رياضي يحاكي الواقع الحالي لاستثمار النبع لفترة زمنية للدراسة تمتد من العام 2009 وهي السنة الأساسية للحسابات ولغاية العام 2030 ، وتبين أنه سوف يحدث عجزاً يبدأ من العام 2010 بمقدار (3 مليون متر مكعب) ويزداد العجز ليصل إلى (46.4 مليون متر مكعب) في العام 2030. ولتلافي حدوث العجز تم وضع سيناريوهات مختلفة لإدارة الاحتياج Demand Management وإدارة التزويد Supply Management مثل سيناريو ترشيد الاستهلاك وتنظيم الضخ، سيناريو تحديد أولويات مواقع الطلب، سيناريو التحكم بغزارة المفيض وتخفيض الهدر إلى البحر، سيناريو استخدام أساليب الري الحديثة وتوفير المياه، وكانت نتيجة هذه السيناريوهات اختفاء العجز بشكل كلي على كامل سنوات الدراسة وتأمين مخزون مياه إضافي للسن يبلغ (100مليون متر مكعب). Sen Spring is one of the most important sources of fresh water in the Syrian Arab Republic, and the primary source in the Syrian Coast to secure drinking water and domestic use of the cities: Lattakia, Tartous, Jableh, Kurdaha, Hafi and many villages affiliate, in addition to securing the needs of agriculture and responsive to the needs of the industry, both for the Banias Refinery or for many of the manufacturers, and the importance of this source of water required to take all measures to protect it from future shortfalls in its ability to supply water quantity and quality and at the right time. So was the use of evaluation and planning system WEAP21 to build a mathematical model that simulates the current reality to invest spring for a time period of the study extends from the year 2009, the base year for calculations until the year 2030. It shows that it will cause a deficit at the start of the year 2010 worth 3 MCM , and this deficit will increase to reach 46.4 MCM in 2030. In order to avoid deficits, different scenarios have been developed for the Demand Management and Supply Management: such as the scenario to rationalize consumption and organize pumping, the scenario to prioritize sites demand, the scenario to control profusely spillway and reduce water that goes into the sea, and the scenario that uses modern irrigation methods and water supply. The result of such scenarios has been the disappearance of the deficits entirely throughout the full years of study and the securing of supplementary water storage to Sen amounting to 100MCM.